Jonathan Edwards: His Holistic Theological Education Legacy of Lights and Shadows - Pazmiño, Robert W.; Esqueda, Octavio J. (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Jonathan Edwards was a colonial pastoral leader and theologian in the United States. Edwards is considered one of the greatest American theologians, excelling as a preacher; however, his importance as a theological educator has received little attention. This conceptual article examines the significance of his educational legacy for Christian educators in the twenty-first century. Edwards espoused holistic theological education with an emphasis on the heart and affections. At the same time, however, he supported slavery, contradicting his theological anthropology. As Christian educators, we would benefit from receiving his invitations, imitating his faith, and learn from his mistakes.